Guns versus Growth: Assessing the Validity of the Benoit Hypothesis on the Egyptian Economy - Elsayed, Mona Rabea Abd Elfattah (International Journal of Economics and Financial Issues, 2024)
In the early 1970s, Emile Benoit introduced the concept of positive correlations between military expenditure rates and economic growth rates in less developed countries (LDCs), igniting interest among development economists. This study evaluates the Benoit hypothesis in the context of the Egyptian economy from 1971 to 2022. Using the Autoregressive Distributed Lag (ARDL) model and the Toda-Yamamoto causality test, we examine the complex dynamics of the, highlighting economic prosperity's influence on defense budgets. However, the absence military spending and economic growth relationship in Egypt. Our findings challenge conventional expectations, revealing intricate short-term and long-term economic interactions. The Toda-Yamamoto test indicates a one-way causal relationship from economic growth to military spendingof a clear reciprocal causal link underscores the relationship's complexity, influenced by factors like resource allocation and temporal lags in the economic impact of military expenditures.